The Low Flow Assessment of Padma River in Bangladesh - Md. Abu Sayed; Aysha Akter (Journal of the Civil Engineering Forum, 2021)
Low flow or Environmental Flow (EF) assessment is vital to ensure the river and ecosystem remain healthy. Both natural and human interventions might alter a river. Therefore, this study presents EF requirements of the famous Hilsa breeding center in the Padma River, Bangladesh, by applying the Hydrologic Engineering Centers River Analysis System (HEC-RAS) for discharge and water surface levels simulations at different stations. The frequency analysis of 20 years of historical data, spanning 2000-2019, used the Log-Pearson Type III (LP-III) distribution method, while the one-dimensional unsteady flow simulation was performed for the last 10 years (i.e., 2012-2019). Subsequently, the HEC-RAS simulated water level values reasonably correlated with the field observations at four stations, namely Baruria Transit, Mawa, Tarpasha, Sureswar, with Coefficient of determination R2=0.86, 0.83, 0.92, and 0.74, alongside simulated minimum water surface levels of 1.57 m, 0.37 m, 0.30 m, and 0.27 m, respectively. Also, the Baruria Transit and Mawa had simulated flows that reasonably correlated with the field observations at R2=0.70 and 0.61, with a simulated minimum flow of 3849.51 m3/s and 3789.14 m3/s, respectively. The minimum flow according to the frequency analysis was 4017 m3/s, 3685 m3/s, 3449 m3/s, 3229 m3/s, and 3113 m3/s at Baruria Transit and 3304 m3/s, 2781 m3/s, 2438 m3/s, 2141 m3/s, 1992 m3/s at Mawa station in 5, 10, 20, 50 and 100 years return periods, respectively. This study overlooked to report the ongoing investigations into the water quality issues. Thus, this study is expected to guide the required EF quantity towards a healthy Hilsha fish habitat and surface water source for drinking purposes in this studied river. The stated method is also applicable to other similar rivers around the world.